Sociodemographic, clinical profile, and psychiatric morbidities among patients with attempted suicide in a tertiary care center: A study from Central India - Sahu, Samiksha; Sahu, R; Agarwal, Jaiprakash; Soni, Ruchi (Industrial psychiatry journal, 2021)
Background: Suicide is a major public health concern and is considered one of the leading causes of death globally. Previous suicidal attempts can be considered as a predictor of underlying psychiatric illness. Identifying factors behind suicidal attempt can help mental health professionals for early diagnosis and treatment as well as designing effective suicide prevention strategies. Aim: The aim of the study is to assess sociodemographic, clinical characteristics, and prevalence of psychiatric morbidities among patients with attempted suicide. Methods: A cross-sectional study was conducted in the emergency department of tertiary care hospital; patients of attempted suicide attending emergency from January 1, 2014, to January 1, 2020, constituted the sample for the study. Data were collected using semi-structured questionnaire which contained sociodemographic and clinical variables. All the subjects were administered mini-international neuropsychiatric interview (MINI), MINI Kid was applied for subjects <18 years, and MINI Plus was applied for subjects above 18 years. Patients were diagnosed according to the ICD-10 Classification of Mental and Behavioral Disorders for research. Results: Suicide attempt was seen more commonly in males, and the most common age group is between 21 and 40 years residing in urban settings. The most common method was consumption of unknown substances (75.35%). Factors leading to suicide are multidimensional in nature. 30.4% of the patients had impulsive traits. 86.5% of people who attempted suicide had a history of psychiatric illness. Detailed assessment of patients for psychiatric illness and psychosocial factors is crucial for planning suicide prevention strategies and policymaking. Conclusions: Young population is at high risk for suicide. More than 80% of these have diagnosable psychiatric illness.